2017
DOI: 10.1016/j.ssmph.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ labor market choices and child development outcomes in Chile

Abstract: This paper examines associations between labor market participation of Chilean mothers and the cognitive, language, and socio-economic development of their children. Using a nationally-representative sample of 3-year-old children, we test if mothers’ work intensity in the two previous years is associated with child development outcomes; data were collected in 2010 when children were one year old, and again in 2012, when they were three years old. We find that children who were three years old with mothers who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
2
12
0
2
Order By: Relevance
“…Maternal characteristics and economic context are well-documented and strong predictors of child development in LMIC (see for example Boo, 2015;Jeong et al, 2017;Paxson & Schady, 2005;Richards et al, 2018;Schady et al, 2015). Previous research from Chile also found that significant relationships between maternal work and child cognitive development were rendered insignificant once other factors were controlled for (Contreras & Gonzalez, 2015;Reynolds et al, 2017). Our analysis and the literature suggests that the vulnerabilities suggested by the bivariate analysis were only reflecting disadvantages of children whose mothers fell into the agricultural, self-employed or single work categories and there is there is no evidence of an additional negative effect of early maternal work once maternal characteristics and economic context are accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal characteristics and economic context are well-documented and strong predictors of child development in LMIC (see for example Boo, 2015;Jeong et al, 2017;Paxson & Schady, 2005;Richards et al, 2018;Schady et al, 2015). Previous research from Chile also found that significant relationships between maternal work and child cognitive development were rendered insignificant once other factors were controlled for (Contreras & Gonzalez, 2015;Reynolds et al, 2017). Our analysis and the literature suggests that the vulnerabilities suggested by the bivariate analysis were only reflecting disadvantages of children whose mothers fell into the agricultural, self-employed or single work categories and there is there is no evidence of an additional negative effect of early maternal work once maternal characteristics and economic context are accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the selected instrument is mothers' premarital labor-force participation captured by a dichotomous variable indicating whether the mother was employed before marriage. A related binary instrument, whether the mother worked before the child was born, has been previously used to instrument maternal employment and is found to predict maternal labor market participation (Reynolds et al, 2017). Because previous work experience has an influence on present and future work participation decisions, the women with higher pre-birth work experience will have higher participation in labor markets following childbirth than women with less experience (McLaughlin, 1982).…”
Section: Empirical Strategymentioning
confidence: 99%
“…This finding was driven by girls and not significant for boys. Reynolds, Fernald, and Behrman (2017) also studied a sample from the Encuesta Longitudinal de la Primera Infancia [Longitudinal Survey of Early Childhood] data set examining the relation between mother's labor market participation and child development outcomes. Taking into account language, cognitive, and socioemotional development, they concluded that in the Chilean population, contrary to several previous results in other samples, children performed better on all these outcomes when mothers participates full-time in the labor market during the first 2 years of life than in cases where mothers worked less.…”
Section: The Encuesta Longitudinal De La Primera Infancia [Longitudinmentioning
confidence: 99%
“…Taking into account language, cognitive, and socioemotional development, they concluded that in the Chilean population, contrary to several previous results in other samples, children performed better on all these outcomes when mothers participates full-time in the labor market during the first 2 years of life than in cases where mothers worked less. Authors indicated that these results may be associated to more access to toys and other resources, and reduced maternal stress (Reynolds et al, 2017).…”
Section: The Encuesta Longitudinal De La Primera Infancia [Longitudinmentioning
confidence: 99%